PENGARUH BUDAYA ORGANISASI DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA PT. PERTAMINA (PERSERO) MARKETING OPERATION REGIONAL I MEDAN - Hidayati, Melly; Nasution, M. Amri; Rahim, Rani (Universitas Dharmawangsa, 2024)
This study aims to examine the influence of organizational culture and leadership on employee performance at PT. Pertamina (Persero) Marketing Operation Regional I Medan. The research utilized a quantitative method with a sample of 52 permanent employees. The analysis techniques included validity and reliability tests, classical assumption tests, multiple regression analysis, t-tests, F-tests, and the coefficient of determination. The findings indicate that both organizational culture and leadership have significant positive effects on employee performance, individually and simultaneously. The coefficient of determination showed that 43.8% of the variation in employee performance can be explained by organizational culture and leadership.